Independent Shifts of Abundant and Rare Bacterial Populations across East Antarctica Glacial Foreland - Yan, Wenkai; Ma, Hongmei; Shi, Guitao; Li, Yuansheng; Sun, Bo; Xiao, Xiang; Zhang, Yu (Frontiers in Microbiology, 2017)
Glacial forelands are extremely sensitive to temperature changes and are therefore appropriate places to explore the development of microbial communities in response to climate-driven deglaciation. In this study, we investigated the bacterial communities that developed at the initial stage of deglaciation using space-for-time substitution in the foreland of an ice sheet in Larsemann Hills. A series of soil samples across the glacial foreland were deeply sequenced with 16S rRNA gene amplicon sequencing to determine the bacterial community, including both abundant bacteria, which contribute more to geobiochemistry, and rare bacteria, which serve as a seed bank for diversity. Our results show that abundant bacterial communities were more sensitive to changing conditions in the early stages of deglaciation than rare community members. Moreover, among the environmental parameters tested, which included total organic carbon, pH, and moisture of the soils, ice thickness was the most influential factor affecting the community structure of abundant bacteria. These results show the different effects of abundant and rare bacteria on community shifts and highlight ice thickness as the primary factor affecting the bacterial community in the early stages of deglaciation. The response of microbial community to climate change can be predicted with more certainty in this polar region.